Assessment of Nutritional Status and Its Determinants among Fewer than 5 Children in a Rural Area of Southern India - Nirmalson, Shini Preetha; Vijayakarthikeyan M (National Journal of Community Medicine, 2022)
Background: Globally malnutrition possesses a double burden in the forms of undernutrition and obesity. The most adverse form of human deprivation is undernutrition among under five children. A child who is underweight may be stunted, wasted or both. Objectives: To assess the nutritional status of under-five children and to identify the determinants of nutritional status among under-five children. Materials and Methods: This is a community based cross-sectional, analytical study conducted on 330 under-five children from a rural area of Salem district of Tamilnadu. Simple random sampling was used to select the study participants. Data was collected using a pre tested semi-structured questionnaire containing socio-demographic particulars, details pertaining to the mother, details pertaining to the child and anthropometric measurements. Data was entered in MS Excel and analysed using SPSS version 20. Results: In this study, majority 60% of them were males. Around 16.4%, 26.4% and 32% of Under 5 children were underweight, wasted and stunted respectively. During the last 1 year about 33.6% and 73.6% had history of acute diarrhoeal infection and acute respiratory tract infection. Variables significantly associated with underweight, stunting and wasting were female gender, nourishment of mother, exclusive breastfeeding (p value < 0.05). Underweight was significantly associated (p value < 0.05) with wasting and stunting. Conclusion: Stunting and wasting rates were higher compared to the National and regional rates given inNFHS-5 data. Proper care of the girl child, frequent sensitization of the mothers regarding the nutrition of their children by community health workers and early diagnosis and treatment of infection are some measures that can be adopted to combat the problem of undernutrition in the locality.